(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A technique for spinning continuous filaments constructed of nano-scale fibers instead of non-woven obtained by general electrospinning was described in the paper. Polyamide 6/66 copolymer solution in 88% formic acid was used as the spinning material. The relationships between the fiber microstructures, filament mechanical properties and spinning parameters: spinneret tip to collector vertical distance (TD), rotation speed (RS) were investigated. Post-drawing was performed to the as-electrospun continuous filament. The research results revealed that increase of TD and RS could improve the fiber’s uniaxial alignment and crystal structure, consequently the strength of the filament was enhanced. After being post-drawn, the stress and strain at break of the electrospun polyamide 6/66 copolymer filament was well improved.